Comparison of thoracic wall behavior in large animals and human cadavers submitted to an identical ballistic blunt thoracic trauma - Prat, Nicolas; Rongieras, Frédéric; de Freminville, Humbert; Magnan, Pascal; Debord, Eric; Fusai, Thierry; Destombe, Casimir; Sarron, Jean-Claude; Voiglio, Eric J. (Forensic science international, 2012)
Several models of ballistic blunt thoracic trauma are available, including human cadavers and large animals. Each model has advantages and disadvantages regarding anatomy and physiology, but they have not been compared with identical ballistic aggression. To compare thoracic wall behavior in 40-kg pigs and human cadavers, the thorax of 12 human cadavers and 19 anesthetized pigs were impacted with two different projectiles at different speeds. On the thoracic wall, the peak acceleration, peak velocity, maximal compression, viscous criterion, and injury criteria (e.g. abbreviated injury scale and number of rib fractures) were recorded. The correlations between these motion and injury parameters and the blunt criterion were compared between the two groups. The bone mineral density of each subject was also measured. The peak acceleration, the peak velocity and the viscous criterion were significantly higher for the pigs. The AIS and the number of rib fractures were significantly higher for human cadavers. The bone mineral density was significantly higher for cadavers, but was, for the two groups, significantly lower than for 30-year-old human. The motion of the pig's thoracic wall is greater than that of the human cadaver, and the severity of the impact is always greater for human cadavers than for pigs. In addition, pig bone is more elastic and less brittle than older human cadaver bone. Due to the bone mineral density, the thoracic wall of human adults should be more rigid and more resistant than the thoracic wall of human cadavers or pigs.